The lacemaker's secret : [large type] : a Chloe Ellefson mystery - Ernst, Kathleen, 1959- (Ernst, Kathleen, 1959- Chloe Ellefson mystery., 2019)
Greed, uncertainty, and death get tangled in the mystery of a rare piece of Belgian lace. Curator Chloe Ellefson needs distraction from the unsettling family secret she's just learned. It doesn't help that her boyfriend, Roelke McKenna, has been troubled for weeks and won't say why. Chloe hopes a consulting job at Green Bay's Heritage Hill Historical Park, where an old Belgian-American farmhouse is being restored, will be a relaxing escape. Instead she discovers a body in a century-old bake oven. Chloe's research suggests that a rare and valuable piece of lace made its way to nearby Door County, Wisconsin, with the earliest Belgian settlers. More importantly, someone is desperate to find it. Inspired by a courageous Belgian woman who survived cholera, famine, and the Great Fire, Chloe must untangle clues to reveal secrets old and new . . . before the killer strikes again.